Phytobezoar: An Unusual Condition Leading to Small Bowel Obstruction - Aydin, Ismail; Sengul, Ilker; Sengul, Demet (Curēus (Palo Alto, CA), 2022)
Bezoar is described as a swallowed, extraneous, and indigestible mass located in the gastrointestinal system; it accounts for 0.4-4.0% of all cases of mechanical intestinal obstruction. Intestinal obstruction is the most frequent complication of bezoar formation. Apart from intestinal obstructions, bezoars may also exhibit clinical symptoms such as abdominal pain, nausea, vomiting, weight loss, upper gastrointestinal bleeding, and gastric perforation. However, a considerable number of cases tend to be asymptomatic. Of note, its clinical symptoms cannot be differentiated easily from intestinal obstructions caused by other factors. As such, preoperative CT examination can provide invaluable information about the level of obstruction, etiology, and the existence of additional pathology and thereby help plan the type of surgical procedure required. If prompt diagnosis and timely treatment are not carried out, the condition may lead to significant morbidity and mortality.